Structural Behaviour Of Pervious Concrete By Using Synthetic Glass Fibre As Reinforcement (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Pervious concrete is a combination of basic concrete material only consisting of cement, coarse aggregate & water. Because pervious concrete will not contains fine aggregate, it is also calledas “nofines ” or “porous” or “permeable “concrete. Pervious concrete also comes under special concretes and willhave more void contentof about 30%. Now a day it is more popular for concrete flat work applications. In this project various literatures has        been studied and understand the effects and application of pervious concrete. The main focus of the project is to investigate the behavior of pervious concrete by using synthetic glass fibre mesh as reinforcement and to improve the flexure behavior. Similarly we canfind the compressive strength comparison of pervious concrete by compression strength test using cube specimen with standard size of 150mm x 150mm x150mm) and flexure strength of the pervious concrete is determined by conducting the flexural test on slab specimen of size (600mm x 300mm x 100mm). The synthetic glass fiber mesh is placed in the slab on three different locations, 1. Bottom of the slab, 2.Top of the slab and 3.Both bottom and top of the slab. The flexural test are carried out on three slab specimen and compare the results for determine the structural behavior of slab using synthetic glass fibermesh.